Lymphatic vessels in cancer - Dieterich, Lothar C; Tacconi, Carlotta; Ducoli, Luca; Detmar, Michael (Physiological reviews, 2022)
The lymphatic system, composed of initial and collecting lymphatic vessels as well as lymph nodes that are present in almost every tissue of the human body, acts as an essential transport system for fluids, biomolecules, and cells between peripheral tissues and the central circulation. Consequently, it is required for normal body physiology but is also involved in the pathogenesis of various diseases, most notably cancer. The important role of tumor-associated lymphatic vessels and lymphangiogenesis in the formation of lymph node metastasis has been elucidated during the last two decades, whereas the underlying mechanisms and the relation between lymphatic and peripheral organ dissemination of cancer cells are incompletely understood. Lymphatic vessels are also important for tumor-host communication, relaying molecular information from a primary or metastatic tumor to regional lymph nodes and the circulatory system. Beyond antigen transport, lymphatic endothelial cells, particularly those residing in lymph node sinuses, have recently been recognized as direct regulators of tumor immunity and immunotherapy responsiveness, presenting tumor antigens and expressing several immune-modulatory signals including PD-L1. In this review, we summarize recent discoveries in this rapidly evolving field and highlight strategies and challenges of therapeutic targeting of lymphatic vessels or specific lymphatic functions in cancer patients.The lymphatic system, composed of initial and collecting lymphatic vessels as well as lymph nodes that are present in almost every tissue of the human body, acts as an essential transport system for fluids, biomolecules, and cells between peripheral tissues and the central circulation. Consequently, it is required for normal body physiology but is also involved in the pathogenesis of various diseases, most notably cancer. The important role of tumor-associated lymphatic vessels and lymphangiogenesis in the formation of lymph node metastasis has been elucidated during the last two decades, whereas the underlying mechanisms and the relation between lymphatic and peripheral organ dissemination of cancer cells are incompletely understood. Lymphatic vessels are also important for tumor-host communication, relaying molecular information from a primary or metastatic tumor to regional lymph nodes and the circulatory system. Beyond antigen transport, lymphatic endothelial cells, particularly those residing in lymph node sinuses, have recently been recognized as direct regulators of tumor immunity and immunotherapy responsiveness, presenting tumor antigens and expressing several immune-modulatory signals including PD-L1. In this review, we summarize recent discoveries in this rapidly evolving field and highlight strategies and challenges of therapeutic targeting of lymphatic vessels or specific lymphatic functions in cancer patients.